Recent developments in severe sepsis research: from bench to bedside and back. (February 2016) - Rasid, Orhan; Cavaillon, Jean-Marc
Severe sepsis remains a worldwide threat, not only in industrialized countries, due to their aging population, but also in developing countries where there still are numerous cases of neonatal and puerperal sepsis. Tools for early diagnosis, a prerequisite for rapid and appropriate antibiotic therapy, are still required. In this review, we highlight some recent developments in our understanding of the associated systemic inflammatory response that help deciphering pathophysiology (e.g., epigenetic, miRNA, regulatory loops, compartmentalization, apoptosis and synergy) and discuss some of the consequences of sepsis (e.g., immune status, neurological and muscular alterations). We also emphasize the challenge to better define animal models and discuss past failures in clinical investigations in order to define new efficient therapies.